Global, regional, and national disease burden attributable to high systolic blood pressure in youth and young adults: 2021 Global Burden of Disease Study analysis - Chuan He; Saien Lu; Haijie Yu; Yingxian Sun; Xueyao Zhang (BMC Medicine)
Abstract Background High systolic blood pressure (HSBP) can cause adverse cardiovascular events and is therefore associated with a heavy global disease burden. However, this disease burden is poorly understood in youth and young adults. We aimed to explore this population to better understand the evolving trends in HSBP-related disease burden, which is crucial for effectively controlling and mitigating harmful effects. Methods This systematic analysis used data from the 2021 Global Burden of Disease Study, spanning 1990–2021. Participants were aged 15–39 years from 204 countries/territories. We analysed HSBP-related disease burden by region, sex, age, and temporal trends. The primary outcomes were disability-adjusted life years (DALYs), mortality rates, and estimated annual percentage change. Results Globally, the number of HSBP-related deaths among youth and young adults has increased by 36.11% (95% uncertainty interval [95% UI], 20.96–52.37%), whereas the number of DALYs has increased by 37.68% (95% UI, 22.69–53.65%); however, global mortality and DALY rates have remained relatively stable. In 2021, the mortality and DALY rates were 4.29 (95% UI, 3.29–5.28) and 263.37 (95% UI, 201.40–324.46) per 100,000 population, respectively. The overall HSBP-related burden was higher in males than in females, with increasing and decreasing trends for males and females, respectively. Regionally, significant improvements in HSBP-related burden were observed in most high-sociodemographic index (SDI) regions, including high-income Asia Pacific (deaths: percentage change, − 72.65%; DALYs: percentage change, − 69.30%) and Western Europe (deaths: percentage change, − 72.89%; DALYs: percentage change, − 67.48%). In contrast, middle-SDI regions had the highest number of deaths and DALYs in 2021, whereas low-middle-SDI regions had the highest mortality and DALY rates. Furthermore, low-SDI regions experienced the largest increase in the number of deaths and DALYs. The HSBP-related burden increased with age; in addition, the proportion of deaths or DALYs due to ischaemic heart disease and stroke increased with age, reaching > 75% for those > 25 years of age. Conclusions The increase in global HSBP-related burden among youth and young adults indicates that current preventative efforts are insufficient. Therefore, targeted measures are needed to counter the trends in HSBP-related diseases and reduce disparities across regions and sexes.